The value of plasma hypoxia markers for predicting imaging-based hypoxia in patients with head-and-neck cancers undergoing definitive chemoradiation. (March 2022) - Rühle, Alexander; Grosu, Anca-L.; Wiedenmann, Nicole; Ruf, Juri; Bieber, Birgit; Stoian, Raluca; Thomsen, Andreas R.; Gkika, Eleni; Vaupel, Peter; Baltas, Dimos; Weber, Wolfgang A.; Mix, Michael; et al.
Highlights: Higher osteopontin plasma levels correlate with more hypoxic tumors at baseline. Increased baseline osteopontin levels are associated with residual tumor hypoxia. Absent early hypoxia response is linked with higher VEGF and CTGF levels in week 5. Plasma hypoxic markers may serve as biomarkers favoring radiotherapy personalization. Abstract: Background: Tumor hypoxia worsens the prognosis of head-and-neck squamous cell carcinoma (HNSCC) patients, and plasma hypoxia markers may be used as biomarkers for radiotherapy personalization. We therefore investigated the role of the hypoxia-associated plasma proteins osteopontin, galectin-3, vascular endothelial growth factor (VEGF) and connective tissue growth factor (CTGF) as surrogate markers for imaging-based tumor hypoxia. Methods: Serial blood samples of HNSCC patients receiving chemoradiation within a prospective trial were analyzed for osteopontin, galectin-3, VEGF and CTGF concentrations. Tumor hypoxia was quantified in treatment weeks 0, 2 and 5 using [ 18 F]FMISO PET/CT. The association between PET-defined hypoxia and the plasma markers was determined using Pearson's correlation analyses. Receiver-operating characteristic analyses were conducted to reveal the diagnostic value of the hypoxia markers. Results: Baseline osteopontin (r = 0.579, p < 0.01) and galectin-3 (r = 0.429, p < 0.05) correlated with the hypoxic subvolume (HSV) prior to radiotherapy, whereas VEGF (r = 0.196, p = 0.36) and CTGF (r = 0.314, p = 0.12) showed no association. Patients with an HSV > 1 mL in week 2 exhibited increased VEGF ( p < 0.05) and CTGF ( p < 0.05) levels in week 5. Pretherapeutic osteopontin levels were higher in patients exhibiting residual hypoxia at the end of treatment (104.7 vs. 60.8 ng/mL, p < 0.05) and could therefore predict residual hypoxia (AUC = 0.821, 95% CI 0.604–1.000, p < 0.05). Conclusion: In this exploratory analysis, osteopontin correlated with the initial HSV and with residual tumor hypoxia; therefore, there may be a rationale to study hypoxic modification based on osteopontin levels. However, as plasma hypoxia markers do not correspond to any spatial information of tumor hypoxia, they have limitations regarding the replacement of [ 18 F]FMISO PET-based focal treatments. The results need to be validated in larger patient cohorts to draw definitive conclusions.